UX research: a flow proposal based on the UA web portal development - Neto, Sydney de Almeida (2021)
As a process inherent to the HCI area, UX Research can be seen as a strategy that supports the development of digital products, namely when usability and accessibility guidelines are used to drive the approach adopted. Practices and strategies based on user experience can facilitate understanding the generation of inputs to drive the digital products development as well as support requirements. In this context, this research is focused on the observation of the UX Research process in the development of the new web portal of the University of Aveiro aiming to investigate how UX Research practice can support the methodological approach used, regarding requirements support, identification of typology interface problems, and collection of information towards the continuous improvement of the development of the University of Aveiro (UA) New Portal. For this purpose, a Mixed Methodology was used based on the Grounded Theory framework, by the inductive process of data observation, delimited to the observation of the new News area of the web portal. Data saturation allowed us to know which UX Research sources had more capacity to raise data from the end-users, support requirements, identify types of interface problems, and supply the development of product solutions. As a consequence of the data processing, this research presents a UXR flow proposal to support data collection and engage stakeholders with the end-user needs and interests.